Antimicrobial, antioxidant, anti-tyrosinase and anti-urease activities and FT-IR analyses of Helichrysum graveolens (Bieb) Sweet - Aydin, Sinem (Bangladesh Journal of Botany, 2019)
Helichrysum graveolens (Bieb) Sweet possesses various medicinal applications such as diuretic, treatment of the sand and stone in kidney, regulation of digestion problems and strenghtening of the immune system. The investigation was carried out to reveal ethanol extracts of flower and stem parts of H. graveolens for antimicrobial, antioxidant, anti-tyrosinase and anti-urease activities. Ethanol extract of stem part of H. graveolens exhibited more antibacterial activity against growth of bacteria except for K. pneumoniae. Stem part of H. graveolens has higher copper reducing antioxidant capacity (CUPRAC) and anti-urease activities than flower part of H. graveolens. Anti-tyrosinase activity (IC50 values) of stem and flower parts of H. graveolens was found to be 0.01549 ± 0.0006 μg/ml and 0.01515 ± 0.0016 μg/ml, respectively. This survey suggests that ethanol extracts of different parts of H. graveolens is an alternative source for natural antioxidant and antimicrobial compounds, urease and tyrosinase inhibitors that could be utilized in drug and food industries.